Answer:
Coin 1 = quarter
Coin 2 = dine
Coin 3 = penny
Step-by-step explanation:
Answer:
-1
Step-by-step explanation:
-5 + 4 = 1
<span> To get an explicit formula, we need to find an expression which gives the n-th term without having to compute earlier terms in the sequence. Looking at the numbers, and from the recursive formula, we see that the sequence is built by subtracting n from the previous term. This is similar to the triangular number sequence 1,3,6,10,15,... which has the explicit formula a_n = n(n+1)/2. In our case we are subtracting n from the previous term, so we multiply by -1/2 instead of 1/2. However, we also need to add a constant term to reproduce the numbers of the sequence. We can write a_1 = -1(2)/2 + c = 8. Therefore, c = 9.
So the explict formula is:
a_n = -n(n+1)/2 + 9</span>
The chance of you selecting one randomly is 4/56, which simplifies to 1/14.
Get it to equal 0
minus 17x from both sides
2x²-17x+35=0
tricky part
get something like
(2x-a)(x-b)
we know the signs are negative since the middle term is negative and last term is positive
so a and b are either 1 and 35 or 5 and 7
(2x-1)(x-35), nope
(2x-35)(x-1) nope
(2x-5)(x-7), nope
(2x-7)(x-5), yep
(2x-7)(x-5)=0
set to zero
2x-7=0
2x=7
x=7/2
x-5=0
x=5
x=7/2 and 5